Sign Language Translator Using KNN - Correia, Steve; Carneiro, Nathen; Barboz, Royce; Naik, Dheeraj; Tuscano, Grinal (Indian Journal of Computer Science, 2024)
Sign language is a profoundly rich and expressive way to communicate, and it is vital for the deaf and hard-of- hearing communities. It provides a distinct avenue for sharing thoughts, feelings, and ideas, helping these individuals to connect and share their viewpoints. Nevertheless, the digital divide remains a significant hurdle, limiting their ability to communicate effectively and integrate fully into a predominantly spoken and written linguistic environment. Our initiative serves as a ray of hope in a time when technology has the potential to close these gaps and promote inclusivity. We are committed to creating a sign language translator powered by Machine Learning. Our main objective is to deliver a real-time translation tool that overcomes these obstacles, facilitating seamless communication between the deaf community and the wider hearing population. By leveraging the power of modern technology, we strive to empower deaf and hard-of-hearing people, enabling them to fully participate in society, access information, and express themselves naturally and inclusively. Our project is a crucial step toward making the world more accessible and fair for everyone.